PENGARUH GENDER DIVERSITY, PROFITABILITAS, UKURAN PERUSAHAAN, UKURAN KAP TERHADAP PENGUNGKAPAN TANGGUNG JAWAB SOSIAL PERUSAHAAN - Ulfa Luthfia Nanda; Gista Rismayani (Jurnal Riset Keuangan dan Akuntansi, 2019)
This paper is aimed to analyse influence of gender diversity, profitability, firm size, audit firm size to corporate social responsibility disclosure. This study use purposive sampling method. Subject of research are food and beverage companies. Sampel of this study are consisted 4 companies which listed in Indonesia Stock Exchange during 2015-2017. Data processing in this study use Software SPSS. Result of examination hypothesis of this study that gender diversity, profitability and audit firm size have no effect significantly on corporate social responsibility disclosure whether firm size have effect significantly on corporate social responsibility disclosure. Keywords :      corporate social responsibility, gender diversity, profitability, firm size, audit firm size